The Influence Of Brand Awareness And E-Service Quality On Consumer Purchasing Decisions In Booking Hotel Rooms On Traveloka - Oktavia, Ria; Budi, Agung Permana; Febianti, Febianti (Institut Pariwisata dan Bisnis Internasional, 2018)
This study was to determine the effect of brand awareness and e-service quality on consumer purchasing decisions in booking hotel rooms in traveloka. The subject of this study amounted to 100 random people who had booked a hotel room through the Traveloka website. The results of the questionnaire were analyzed using multiple linear regression to see the effect between variable brand awareness, e-service quality and purchasing decisions. The results of this study indicate that brand awareness and e-service quality have a significant effect of 67.1% on the variables of consumer purchasing decisions in hotel room bookings, on the traveloka website. The implication of this research is to see the contribution of the variables studied to be used as consumer decisions in making purchases on room sales services on the website, so marketing is important to know.